Grief Workshop - Anasuya, Jegathevi Jegathesan (2014)
Grief Workshop conducted by Dr Anasuya Jegathevi Jegathesan for 1st Malaysia International Counselling Conference (MICC 2014). The workshop covers loss and grief terminology,motions experienced in grief, normal and complicated grief and contemporary models of loss adaptation.